Answer:
Step-by-step explanation:
we have to use the formula of slope here.
we know,
slope of the line passing through (x1,y1) and (x2,y2) is-
![\frac{y2-y1}{x2-x1}](https://tex.z-dn.net/?f=%5Cfrac%7By2-y1%7D%7Bx2-x1%7D)
Here, the first two points are -
(-4 , 5) and (0,6)
So, the slope will be-
![\frac{6-5}{0-(-4)}=\frac{1}{0+4}=\frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B6-5%7D%7B0-%28-4%29%7D%3D%5Cfrac%7B1%7D%7B0%2B4%7D%3D%5Cfrac%7B1%7D%7B4%7D)
So, the slope is-
![\frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D)
Answer:
Step-by-step explanation:
x
y
−
4
0
−
3
1
−
3
−
1
−
2
2
−
2
−
2
Answer:
The equivalent expression to the given expression is ![\sqrt[3]{32x^8y^{10}}=2x^2y^3\sqrt[3]{4x^2y}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B32x%5E8y%5E%7B10%7D%7D%3D2x%5E2y%5E3%5Csqrt%5B3%5D%7B4x%5E2y%7D)
Step-by-step explanation:
The given expression is ![\sqrt[3]{32x^8y^{10}}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B32x%5E8y%5E%7B10%7D%7D)
To find the equivalent expression:
![\sqrt[3]{32x^8y^{10}}=(32x^8y^{10})^{\frac{1}{3}}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B32x%5E8y%5E%7B10%7D%7D%3D%2832x%5E8y%5E%7B10%7D%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D)
We may write the above expression as below:
![=(32^{\frac{1}{3}})((x^8)^{\frac{1}{3}})((y^{10})^{\frac{1}{3}})](https://tex.z-dn.net/?f=%3D%2832%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%29%28%28x%5E8%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%29%28%28y%5E%7B10%7D%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%29)
(using square root properties)
(combining the like terms and doing multiplication )
Therefore ![\sqrt[3]{32x^8y^{10}}=2x^2y^3\sqrt[3]{4x^2y}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B32x%5E8y%5E%7B10%7D%7D%3D2x%5E2y%5E3%5Csqrt%5B3%5D%7B4x%5E2y%7D)
Therefore the equivalent expression to the given expression is ![\sqrt[3]{32x^8y^{10}}=2x^2y^3\sqrt[3]{4x^2y}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B32x%5E8y%5E%7B10%7D%7D%3D2x%5E2y%5E3%5Csqrt%5B3%5D%7B4x%5E2y%7D)
Answer:
nice no questions
=)
Step-by-step explanation: